2017
DOI: 10.9734/ijpss/2017/35037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seed Transmission of Rhizoctonia solani and Seed Mycoflora of Ajwain

Abstract: In vitro study was conducted Department of Plant Pathology, Rajasthan College of Agriculture, Udaipur (Rajasthan) and evaluated the seed transmission of R. solani from the seeds of eight popular cultivars of ajwain viz., Ajmer Ajwain-1, Ajmer Ajwain-2, Ajmer Ajwain-93, Pratap Ajwain, Lam selection-1, Gujarat Ajwain-1, Azad Ajwain and local cultivar. It was found that maximum recovery of the pathogens was from local cultivar and Ajmer Ajwain-93 exhibited lowest recovery of pathogens. It was also found in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Among the various microorganism, fungi are important causative factors of deterioration that bring about several undesirable changes during storage, spoiling the quality of seeds by discolouration and altering the biochemical constituents. A perusal of literature revealed that mycoflora associated with ajwain seeds has been studied (Manjari et al 1996;Lal et al 2013;Fagodia et al 2017) but only a meager work has been reported on the qualitative aspect of ajwain related to storage conditions. Hence, the effect of different types of storage conditions on quality of ajwain was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various microorganism, fungi are important causative factors of deterioration that bring about several undesirable changes during storage, spoiling the quality of seeds by discolouration and altering the biochemical constituents. A perusal of literature revealed that mycoflora associated with ajwain seeds has been studied (Manjari et al 1996;Lal et al 2013;Fagodia et al 2017) but only a meager work has been reported on the qualitative aspect of ajwain related to storage conditions. Hence, the effect of different types of storage conditions on quality of ajwain was investigated.…”
Section: Introductionmentioning
confidence: 99%